Condensation and thermophysical properties of R1336mzz(Z) through molecular dynamics simulations. (February 2023) - Khan, Misbah; Wen, Jian; Shakoori, Muhammad Asif; Liu, Yuce
Abstract: Hydrofluoroolefins (HFOs) are the latest refrigerants with promising low global warming potential and zero Ozone depletion potential used as an alternative to hydrofluorocarbon (HFC). The HFO [R1336mzz(Z)] is a drop-in replacement of HFC [R245fa] and is considered as working fluid of the Organic Rankine Cycle, heat pumps etc. The focus of this study to evaluate the homogeneous condensation, thermophysical and structural properties of R1336mzz(Z) through Molecular Dynamics (MD) simulations. Results were computed for a wide range of condensation temperatures (T = 273.15-343.15 K) and pressures (P = 0.5-4.0 MPa) by keeping a constant number of molecules. MD simulations provide thermophysical properties such as liquid density and isobaric heat capacity, internal potential energy, mean square displacement and volume for R1336mzz(E) and R245fa at nearly the same values of condensation temperature and pressures were compared and discussed with each other. In addition, the calculated liquid density and isobaric heat capacity of both R1336mzz(Z) and R245fa were compared with NIST REFPROP 10.0 and experimental data. The dynamical properties of both and the structural properties of R1336mzz(E) during the condensation process were discussed and analyzed. There is no affect observed on the intramolecular structure of R1336mzz(Z) during the condensation phenomena. The presented results demonstrate that R1336mzz(Z) has a significantly lower condensation rate from moderate to higher temperatures than R245fa and the condensation rate increased with increasing temperature and decreasing pressures. The MD and REFPROP data show that both refrigerants have nearly the same density and isobaric heat capacity values.